Normas aplicables en el marco jurídico de compraventa internacional. - Banegas Ogoño, Diana Del Carmen (My University, 2019)
International trade is a sector in frank growth caused by the phenomenon of globalization in which almost all the nations of the world are involved, provoking the social and economic development of the countries involved. The development of foreign trade has led to the presence of international standards in order to ensure trade where the exporter and importer to close their negotiations need legal regulations that protect them respecting their rights and obligations to which they are subject. that is why the Vienna Convention on the International Sale of Goods creates an organization that promotes the good of international trade, serving as a reference for international trade regulations, to which exporters and importers can subject themselves, when a conflict may arise. between the parties for breach of contract. The objective of the work is to determine the applicable norms in the contracts of international merchandise sales according to the UNIDROIT principles. The methods used to carry out the research was the documentary type, based on the accumulation of useful information of validated web portals, magazines and books. . The importance of the work is given by the need for the exporter and importer to know their rights and obligations, going to local and international organizations when they believe that their rights have been violated. The emphasis in the work is on the importer, in which the regulations that cover it are exposed so that their commercial activities are respected.
El comercio internacional es un sector en franco crecimiento provocado por el fenómeno de la globalización en que están inmiscuidas casi todas las naciones del mundo, provocando el desarrollo social y económico de los países involucrados. El desarrollo del comercio exterior ha dado lugar a la presencia de normas internacionales con la finalidad de garantizar el comercio donde el exportador e importador al cerrar sus negociaciones necesitan de normativas legales que les de protección respetando sus derechos y obligaciones a las que están sujetos.Es por esto que la Convención de Viena sobre Compraventa Internacional de Mercaderías crea una organización que promueva el bien del comercio internacional, sirviendo como un referente de las normativas internacionales de intercambio comercial, a los que pueden sujetarse los exportadores e importadores, cuando pueda presentarse un conflicto entre las partes por el incumplimiento del contrato. El objetivo del trabajo es determinar las normas aplicables en los contratos de compraventa internacional de mercancías según los principios UNIDROIT Los métodos usados para llevar a cabo la investigación fue el tipo documental, basado en la acumulación de información útil de portales web validados, revistas y libros. La importancia del trabajo se da por la necesidad de que el exportador e importador conozcan de sus derechos y obligaciones, acudiendo a los organismos locales e internacionales cuando crean que se han visto vulnerados sus derechos. En el trabajo se hace énfasis en el importador, en que se exponen las normativas que lo cobijan para que se hagan respetar sus actividades comerciales.
Keywords: COMERCIO INTERNACIONAL; EXPORTADOR; IMPORTADOR; CONTRATO COMPRAVENTA; DERECHOS DEL IMPORTADOR